1985
DOI: 10.1097/00004032-198504000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Emanation Coefficients for Rn in Sized Coal Fly Ash

Abstract: Emanation coefficients for 222Rn in sized samples of dry coal fly ash were evaluated as a function of source and particle size using a modification of the "sealed-can, gamma-only" technique. The emanation coefficient is defined as the fraction of Rn atoms that escape the solid particles of a source. Diffusible Rn was separated from nondiffusible Rn by adsorption on charcoal, and each was measured independently by gamma-ray spectrometry of the Rn daughter, 214Bi. Samples of ash from eastern bituminous coal, wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…This should be attributed to the smaller grain size of the fly-ash collected there, which results in an increase of the surface-to-volume-ratio that allows for higher radon emanation power. These conclusions are consistent with those of Kalkwarf et al (1985), who have determined the emanation coefficient of 222 Rn for fly-ash samples of different origin, as a function of their size, and concluded that emanation coefficients depend both on the source and the size of fly-ash, and furthermore they generally decrease monotonically with increasing particle size. 3.…”
Section: Radon Exhalation Measurements Of Lignite and Ashessupporting
confidence: 91%
“…This should be attributed to the smaller grain size of the fly-ash collected there, which results in an increase of the surface-to-volume-ratio that allows for higher radon emanation power. These conclusions are consistent with those of Kalkwarf et al (1985), who have determined the emanation coefficient of 222 Rn for fly-ash samples of different origin, as a function of their size, and concluded that emanation coefficients depend both on the source and the size of fly-ash, and furthermore they generally decrease monotonically with increasing particle size. 3.…”
Section: Radon Exhalation Measurements Of Lignite and Ashessupporting
confidence: 91%
“…Duport and Edwardson (1984) reported values between 0 and 0.5 for micron-sized samples of uranium ore dust. Kalkwarf et al. (1985) measured radon emanation coefficients in the range 0.001–0.1 for coal fly ash particles in sized fractions from less than 0.5 µm to 11–15 µm.…”
Section: Thorium (Z = 90)mentioning
confidence: 98%
“…Among building materials, natural marble is in common use [4][5][6][7][8]. Long-term whole-body exposure to radiation due to the use of such granite and marble materials in Symmetry 2020, 12, 1219 2 of 21 buildings can affect the health of the individuals using them [9,10]. Therefore, it is very important to compare the natural radioactivity levels of marble ( 226 Ra, 232 Th, and 40 K) and their associated radiological impact indexes with the accepted limit values.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to reveal the reason why the radioactivity of the samples depends on the grain size. Some differences may be observed depending on the type of sample investigated [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%